The effects of CWI and CWT on performance recovery following high-intensity exercise: A systematic review and meta-analysis - Graham, A. (Journal of Australian Strength and Conditioning, 2017)
The aim of this systematic review was to determine the effects of cold water immersion (CWI) and contrast water therapy (CWT) on the recovery of athletic performance following high-intensity exercise.